HUBUNGAN ANTARA PERSEPSI TENTANG KONDISI FISIK LINGKUNGAN KERJA DENGAN SIKAP KERJA DALAM MENINGKATKAN ETOS KERJA KARYAWAN UD. ES WE DI SURAKARTA - Sunaryo, Adet Setyadi (TALENTA, 2013)
Problems that may impede the achievement of the corporate objectives owned work ethic of its employees , as the companys goals can be achieved optimally require employees who have a high work ethic that allows a company to maintain its existence . Objectives to be achieved in the study was to determine whether there is a significant relationship between the perception of the physical condition of the work environment, employee attitudes and work ethic UD employees. ES WE Surakarta . The study population was a production employee UD. ES WE Surakarta. Samples taken the number of production employees 42 people. Measuring instruments used are scale perception of the work environment, employee attitudes and work ethic of employees. Results of F-test or ANOVA shows that the work environment and work attitudes have a close relationship to the work ethic of employees with known Fhitung > F on confidence level Î± = 5 % isÂ  equal to 96.776 > 2.83. Ha received means that the work environment and employee attitudes significantly affect the work ethic in UD production employees. ES WE Surakarta.